Electro-Acoustic Factors Determining Telephone Speech Quality - Gruber, J.; Bhullar, J.; Williams, G. (Canadian Acoustics, 1982)
In this paper the electro-acoustic factors affecting the quality of telephone speech are categorized as: - listening factors such as loudness, noise, frequency response, and listener echo, - talking factors such as talker echo and sidetone, and - conversational factors such as delay. Listening factors in particular are emphasized and qualitatively interpreted in terms of acoustic pressures at the ear relative to the thresholds of hearing and pain. Typical telephone connections are then considered in which a number of the above factors are manifested; this is done in the context of a network simulation facility used by Bell-Northern Research to simulate various telephone network impairments for the purposes of objective and subjective evaluation. Grade^of-service results that relate customer opinion of transmission quality to the level of a transmission parameter are also discussed. These include listener echo and delay, and subjective-equivalence modelling of speech-correlated digital noise in terms of continuous analog noise.